Editorial - Miranda, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
There are various limitations that production systems face to become a consolidated production chain, much more when adopting technologies from different agroecological conditions, the lack of profiles of its actors and the absence of infrastructure to develop. Latin America contains many examples that have been widely studied in the literature.